Credits, social policies, and consumption in Buenos Aires City - Chahbenderian, Florencia (2023)
At the turn of the twenty-first century, social policies became one of the fundamental instruments on which the current capital accumulation regime is based, given their massive nature and global character. So-called conditional cash transfer programs (CCTs) were a milestone in this direction. The objective of this article is to study the consumption practices – the what and how – that CCTs impose on their recipients and the latter’s relationship with credit in Buenos Aires City. The qualitative methodology is based on documentary analysis and semistructured interviews with CCT recipients and public servants. The implications for social policies can be summarised as: (a) re-thinking the links between the market and the State, as these regulations involve politics of the body/emotions; and (b) deepening the connections between social policies (in the form of CCTs), consumption, and credit.